Hubungan Tingkat Pengetahuan Dengan Kepatuhan Diet Pada Penderita Diabetes Mellitus Tipe II Di Puskesmas Cengkareng Jakarta Barat - Vika Rosmeri; Asrifah Suardi (Jurnal Anestesi, 2023)
Diabetes mellitus is a serious threat to health development because it can cause complications so it needs to be managed, one of which is diet management. Proper diet helps control blood sugar so it doesn't spike high. The purpose of this study was to determine the relationship between knowledge level and dietary adherence in diabetics. type 2 mellitus at the Cengkareng Health Center. This study used a cross-sectional approach, a sample of 30 people with a total sampling that met the inclusion and exclusion criteria. ), 19 people (63.3%) lack knowledge, while 1 person (3.3%) adheres to a good diet, 20 people (66.7%) suffice and 9 people lack (30.0). Based on the results of the analysis that has been carried out for the level relationship knowledge with dietary compliance with type II diabetes mellitus at the Cengkareng Health Center, West Jakarta, obtained pvalue = 0.034 with the results of the test using Chi-Square, and from these results there is a relationship between the level of knowledge and dietary compliance which has a significant relationship (p <0.05 ). It is hoped that health workers will continue to motivate and provide education to diabetics about diabetes mellitus and dietary compliance.